X=6 is the answer for the problem
Answer:
I hope I know but I need help my self
Answer:
Step-by-step explanation:
10: B
11: A
Given:
The function is
![f(x)=-3x^2+2x-7](https://tex.z-dn.net/?f=f%28x%29%3D-3x%5E2%2B2x-7)
To find:
The value of f(-1).
Solution:
We have,
![f(x)=-3x^2+2x-7](https://tex.z-dn.net/?f=f%28x%29%3D-3x%5E2%2B2x-7)
Putting x=-1, we get
![f(-1)=-3(-1)^2+2(-1)-7](https://tex.z-dn.net/?f=f%28-1%29%3D-3%28-1%29%5E2%2B2%28-1%29-7)
![f(-1)=-3(1)-2-7](https://tex.z-dn.net/?f=f%28-1%29%3D-3%281%29-2-7)
![f(-1)=-3-9](https://tex.z-dn.net/?f=f%28-1%29%3D-3-9)
![f(-1)=-12](https://tex.z-dn.net/?f=f%28-1%29%3D-12)
Therefore, the value of f(-1) is -12.
Answer:
![\Huge\boxed{\mathsf{\Rightarrow X>-5}}}](https://tex.z-dn.net/?f=%5CHuge%5Cboxed%7B%5Cmathsf%7B%5CRightarrow%20X%3E-5%7D%7D%7D)
Step-by-step explanation:
Isolate x on one side of the equation.
First, subtract 7 from both sides.
x+7-7>2-7
Solve.
2-7=-5
x>-5
So, the final answer is x>-5.